Perbandingan Perubahan Warna Resin Aklirik (Heat Cured) Dan Thermoplastic Nylon Terhadap Perendaman Teh Hijau - Caezar, Herautami; Susanto, Husein Silalahi; Gustina, Mara; Mayangsari, Nino; S, Rudy; Lukis, Prima Agusti (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2024)
Abstract Background: Denture base materials, acrylic and thermoplastic nylon, have the disadvantage of high water absorption. Green tea contains tannins wich can cause discoloration of the denture base. Objective: To compare the magnitude of the color change in heat cured acrylic resin and thermoplastic nylon after being soaked in green tea. Method:The design of this research is laboratory experimental with a pretest and posttest only control group design, consisting of 2 groups. Group 1 is resin acrylic and Group 2 is thermoplastic nylon, both were soaked in green tea for 7 days. The samples were measured using a spectrophotometer. Results were analyzed using One Way ANOVA. Results: Based on the One-Way ANOVA test, it is known that the p-value of 0.000 is smaller than 0.05 (p < 0.05). so it can be said that there is a significant difference in color change of resin and thermoplastic nylon denture bases after being soaked in green tea. Conclusion: Thermoplastic nylon absorbs more color agent (tannis) compared to acrylic resin Keywords: Acrylic resin, Thermoplastic nylon, Green tea, Color change